2017
DOI: 10.3748/wjg.v23.i33.6030
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis: Standard treatment and systematic review of alternative treatments

Abstract: Autoimmune hepatitis is a rare chronic inflammatory liver disease, affecting all ages, characterised by elevated transaminase and immunoglobulin G levels, positive autoantibodies, interface hepatitis at liver histology and good response to immunosuppressive treatment. If untreated, it has a poor prognosis. The aim of this review is to summarize the evidence for standard treatment and to provide a systematic review on alternative treatments for adults and children. Standard treatment is based on steroids and az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
28

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 164 publications
(172 reference statements)
2
103
0
28
Order By: Relevance
“…40 Prednisone and azathioprine are first line therapies, while CsA and mycophenolate are used as rescue agents or in cases refractory to prednisone and azathioprine. 39,40 There is no standardized criteria for the diagnosis of autoimmune hepatitis in dogs or consensus on the best therapeutic approach for suspected immune hepatitis in dogs. Two retrospective studies looking at the use of corticosteroids to treat CH in dogs have suggested that some dogs do have a positive response to therapy and thus meet one of the diagnostic criteria for immune mediated disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Prednisone and azathioprine are first line therapies, while CsA and mycophenolate are used as rescue agents or in cases refractory to prednisone and azathioprine. 39,40 There is no standardized criteria for the diagnosis of autoimmune hepatitis in dogs or consensus on the best therapeutic approach for suspected immune hepatitis in dogs. Two retrospective studies looking at the use of corticosteroids to treat CH in dogs have suggested that some dogs do have a positive response to therapy and thus meet one of the diagnostic criteria for immune mediated disease.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the diagnostic criteria for autoimmune hepatitis are clearly established and scored based on the following features: elevated serum ALT, the presence of positive serum autoantibodies titers, elevated serum immunoglobulin G, characteristic histopathology findings (interface hepatitis), and the exclusion of other etiologies such as viral and alcoholic hepatitis. 39,40 Although medical records were comprehensively and expertly reviewed, it is possible given the retrospective nature of the study that some cases were not truly idiopathic CH. Remission criteria are also standardized in humans and include normalization of serum ALT, bilirubin and IgG, alleviation of clinical symptoms, and return to normal hepatic tissue on histopathology.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the evidence of second-line drugs in AIH treatment is mainly based on small, retrospective case series [59,63]. The available evidence does not allow a recommendation as to which of the possible second-line drugs should be preferred [36].…”
Section: The Stepwise Medication Choice In the Treat-to-target Strategymentioning
confidence: 99%
“…Steroid which may have a more rapid action than immunosuppressive agents is usually administered during the induction-remission phase. For patients who do not respond or are intolerant to standard treatment, second-line drugs including budesonide, mycophenolate mofetil, the calcineurin inhibitors (cyclosporine and tacrolimus) and biologicals (rituximab and infliximab) have been used as alternative choice in AIH [55][56][57][58][59]. Mycophenolate mofetil is the most widely used second-line drug.…”
Section: The Stepwise Medication Choice In the Treat-to-target Strategymentioning
confidence: 99%